Novel current-limiting strategy for solid-state circuit breakers (SSCB) without additional impedance - Gu, Chunyang; Effah, Francis Boafo; Castellazzi, Alberto; Watson, Alan James; Wheeler, Patrick (2016)
Current-limiting strategies for solid-state circuit breaker (SSCB) without adding impedance is introduced in this paper. With the current limitation of novel phase-shifting method, the advantages are simple hardware structure, relatively low cost, no heat generation, low weight and small size. Current-limiting capability is exploited with qualities of good control accuracy and robustness. The principle and theoretical analysis of phase-shifting current-limiting method are detailed introduced together with simulation/experimental verifications.